A Linguistic and Cultural Perspective on Lexical Semantics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The subject of lexical semantics is becoming increasingly important in modern linguistics. The in-depth investigation of the system and structural structure of current English language is particularly important in this regard. The latter contains a range of verbal tools for transferring, revealing, and even changing the current ones, replacing them with freshly formed words and their meanings. English, like every other language, has its own system and structure, as well as elements that are arranged in a hierarchical order inside its semantic space. The complex examination of lexico-semantic distinctiveness of words allows for a more in-depth investigation of the most important aspects of corresponding national cultures.